Case report: Down syndrome regression disorder, catatonia, and psychiatric and immunomodulatory interventions - Connors, Michael H.; Sachdev, Perminder S.; Colebatch, James G.; Taylor, Mark S.; Trollor, Julian; Mohan, Adith (Frontiers in Psychiatry, 2024)
Down syndrome regression disorder (DSRD) is a rare condition involving subacute cognitive decline, loss of previously acquired developmental skills, and prominent neuropsychiatric symptoms, particularly catatonia, in people with Down syndrome. It is thought to involve both autoimmune and neuropsychiatric mechanisms. Research, however, is largely restricted to case studies and retrospective case series and is particularly limited in terms of prospective longitudinal follow-up. We report a case study of a person with DSRD who received both immunomodulatory (intravenous immunoglobulin; IVIG) and psychiatric interventions (electroconvulsive therapy, ECT) over two years with regular assessments using caregiver and clinician ratings. This revealed a small, unsustained response to IVIG and a rapid, sustained response once ECT was introduced. The case highlights the importance of multimodal assessment involving multiple medical specialties, the need to trial different therapies due to the condition’s complexity, and the significant barriers that patients and their families face in accessing care.